2011
DOI: 10.4067/s0717-66432011000200015
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of tree seedling mortality in a temperate-mediterranean transition zone forest in Chile

Abstract: Seedling mortality in forests is the net result of an array of processes that vary spatially and temporally. We quantified emergence and mortality of seedlings at monthly intervals for two years, in a forest situated in the transition zone between the Mediterranean and temperate regions of Chile. We aimed to determine if survival of species responded differentially to seasonal water availability, to the spatial variation in light availability and to seedling density. The commonest species in the seedling bank … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 31 publications
(32 reference statements)
1
5
0
Order By: Relevance
“…This finding supported the research by Galiano et al [45] and Parada and Lusk [46], which explored how drought or reduced rainfall limited the survival of plants at the seedling stage. In comparison with other studies, the density of natural regeneration at our study sites was lower than that of semi-evergreen forests in Myanmar studied by Oo [47], and higher than that of the secondary forests in Vietnam studied by Woo et al [48].…”
Section: Discussionsupporting
confidence: 88%
“…This finding supported the research by Galiano et al [45] and Parada and Lusk [46], which explored how drought or reduced rainfall limited the survival of plants at the seedling stage. In comparison with other studies, the density of natural regeneration at our study sites was lower than that of semi-evergreen forests in Myanmar studied by Oo [47], and higher than that of the secondary forests in Vietnam studied by Woo et al [48].…”
Section: Discussionsupporting
confidence: 88%
“…High levels of C storage could be advantageous to recover from drought and fire, which are main causes of seedling mortality in Mediterranean forests. Furthermore, drought and shade tolerance were found to be unrelated in Mediterranean forests (Sánchez‐Gómez et al, 2006), even with similar climate and physiognomy to the one I studied (Parada and Lusk, 2011). Likewise, shade tolerance and fire resistance are not apparently related in the Mediterranean species studied here, because resprouting has been reported in both highly shade tolerant and intolerant species (Veblen et al, 1979; González et al, 2002; Donoso, 2006).…”
Section: Discussionmentioning
confidence: 59%
“…In contrast to the temperate rain forest sites, we found that woody species in the Mediterranean forest we surveyed did not partition the fine-scale gradient in light availability. This is most probably because, unlike temperate rain forests, regeneration in Mediterranean forests is most strongly limited by water rather than light availability (Parada and Lusk, 2011), or perhaps regeneration here is mediated by traits other than LMA. In fact, the range of GLI values found in this Mediterranean forest (50 %) was considerably lower than in the temperate rain forests (80 %).…”
Section: Discussionmentioning
confidence: 94%